1985
DOI: 10.1095/biolreprod32.3.480
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Luteinizing Hormone-Induced Increase of Ovarian Blood Flow During the Estrous Cycle in the Rat

Abstract: CYF rats were anesthetized on various days of the 4-day cycle and blood samples were collected at 5-min interals from the ovarian vein before and after i.v. administration of 5 micrograms/100 g BW of luteinizing hormone (LH). Ovarian venous outflow, blood pressure and hematocrit were continuously recorded, and from the blood samples progesterone (P) and 17 beta-estradiol (E2) were determined by radioimmunoassay (RIA). Ovarian blood flow and P secretion showed a parallel increase on Day 1 (estrus), on Day 2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…In the previous studies in cattle (Acosta et al 2003), rats (Varga et al 1985), rabbits (Janson 1975) and sheep (Niswender et al 1976), the role of oestradiol and LH on blood flow of the follicle wall was not well established. An increase of blood-flow velocity (TAMV) in the vessel of the follicular wall occurred 0.5 h after GnRH treatment, synchronously with an increase in systemic concentrations of oestradiol and LH (Acosta et al 2003); follicular blood flow remained high, while systemic concentrations of oestradiol and LH returned to basal level by 6 h and remained low until ovulation.…”
Section: Discussionmentioning
confidence: 97%
“…In the previous studies in cattle (Acosta et al 2003), rats (Varga et al 1985), rabbits (Janson 1975) and sheep (Niswender et al 1976), the role of oestradiol and LH on blood flow of the follicle wall was not well established. An increase of blood-flow velocity (TAMV) in the vessel of the follicular wall occurred 0.5 h after GnRH treatment, synchronously with an increase in systemic concentrations of oestradiol and LH (Acosta et al 2003); follicular blood flow remained high, while systemic concentrations of oestradiol and LH returned to basal level by 6 h and remained low until ovulation.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, a beta adrenergic mechanism is involved in steroid-induced increases in ovarian blood flow (Varga et al, 1985) as well as in the facilitation of LH-induced steroidogenesis in hypertrophied thecal and secondary interstitial cells (Erickson et al, 1985). Moreover, these cells have been shown to receive direct adrenergic innervation (Erickson et al, 1985).…”
mentioning
confidence: 99%
“…The estrogen concentration appears to be only one of many factors that affect follicular blood flow; our results showed that follicular blood flow continued to increase from Day -1 to Day 0 in the 1 st wave cycles even though the concentration of estrogen decreased during the same time period. For example, it has been demonstrated that LH induces an increase in follicular blood flow in rats by decreasing vascular resistance in the rat ovary [23]. Furthermore, the results of several studies indicate that there is crosstalk between vascular components (endothelial cells) and follicular steroidogenic cells [24,25] that may modulate the local changes of blood flow in ovulatory follicles [26].…”
Section: Discussionmentioning
confidence: 99%